Post-COVID 19 Strategy Development for Bamboo Handicraft Sub-Sector in Selaawi Garut, Indonesia - Irfan Nabhani; Risa Aisyah (Jurnal Wacana Ekonomi, 2022)
Bamboo in Selaawi is very important element for the community, providing basic needs such as housing and furniture, as well as providing major economic contribution from bamboo crafts as a main commodity of this municipality; as happened to the most industries, bamboo handicraft also got a big hit by the pandemic. A comprehensive study was conducted to analyse and identify the fittest strategy in order to establish a more resilient bamboo handicraft business. This study applied a qualitative method to identify and analyse the SWOT of the business based on some literature reviews to understand the theoretical basis prior conducting in-depth interviews with 8 respective stakeholders and questionnaire to 30 craftsmen in this specific area. Based on the result and discussion, apart from normative strategy such as product differentiation, optimizing e-commerce, productivity and profitability improvement this study revealed that a collaboration of eco-edu-tourism should be introduced as another strategy approach to create a more resilient bamboo handicraft industry.